2020
DOI: 10.1371/journal.pone.0236009
|View full text |Cite
|
Sign up to set email alerts
|

Voice quality and speech fluency distinguish individuals with Mild Cognitive Impairment from Healthy Controls

Abstract: Mild Cognitive Impairment (MCI) is a syndrome characterized by cognitive decline greater than expected for an individual's age and education level. This study aims to determine whether voice quality and speech fluency distinguish patients with MCI from healthy individuals to improve diagnosis of patients with MCI. We analyzed recordings of the Cookie Theft picture description task produced by 26 patients with MCI and 29 healthy controls from Sweden and calculated measures of voice quality and speech fluency. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 60 publications
1
58
0
Order By: Relevance
“…A growing body of work is highlighting the ongoing clinical validation of speech-based measures in a variety of clinical contexts. Speech has been demonstrated to have diagnostic validity for Alzheimer's disease (AD) and mild cognitive impairment (MCI) in studies using machine-learning classification models to differentiate individuals with AD/MCI from healthy individuals based on speech samples [34][35][36][37][38][39][40][41]. Additionally, speech analysis has been shown to be able to detect individuals with depression [42][43][44][45], schizophrenia [46][47][48][49], autism spectrum disorder [50], and Parkinson's disease [51,52], and can differentiate the subtypes of primary progressive aphasia and frontotemporal dementia [53][54][55].…”
Section: Clinical Validationmentioning
confidence: 99%
“…A growing body of work is highlighting the ongoing clinical validation of speech-based measures in a variety of clinical contexts. Speech has been demonstrated to have diagnostic validity for Alzheimer's disease (AD) and mild cognitive impairment (MCI) in studies using machine-learning classification models to differentiate individuals with AD/MCI from healthy individuals based on speech samples [34][35][36][37][38][39][40][41]. Additionally, speech analysis has been shown to be able to detect individuals with depression [42][43][44][45], schizophrenia [46][47][48][49], autism spectrum disorder [50], and Parkinson's disease [51,52], and can differentiate the subtypes of primary progressive aphasia and frontotemporal dementia [53][54][55].…”
Section: Clinical Validationmentioning
confidence: 99%
“…The reduction in speech expressiveness during picturedescription tasks has also been quantified by measuring speech rate as well as the reduction in relevant information (18,(24)(25)(26)(27). By using a combination of these features, previous studies have succeeded in differentiating AD and MCI patients from healthy controls (20,21,24,25,(28)(29)(30)(31). However, they mainly investigated speech data obtained while participants took part in neuropsychological tasks, typically conducted by clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…The recordings were conducted in an isolated environment at the University of Gothenburg. The recordings were analyzed acoustically, using advanced acoustic analysis and signal processing algorithms (see for the methodological analysis (Themistocleous et al, 2020)).…”
Section: Methodsmentioning
confidence: 99%
“…These results suggested that the accuracy of traditional screening tools may be improved through the addition of computerized language analysis. In this study, our goal is to determine whether cognitive decline can be estimated using acoustic information, as we have shown that speech production is impaired in patients with MCI , 2020. Thus, contributing to the work of identifying automatic diagnostic markers that have the potential to facilitate clinical evaluation and therapy.…”
Section: Introductionmentioning
confidence: 99%